2022
DOI: 10.3389/fped.2022.1024566
|View full text |Cite
|
Sign up to set email alerts
|

Could Near Infrared Spectroscopy (NIRS) be the new weapon in our fight against Necrotising Enterocolitis?

Abstract: There is no ideal single gut tissue or inflammatory biomarker available to help to try and identify Necrotising Enterocolitis (NEC) before its clinical onset. Neonatologists are all too familiar with the devastating consequences of NEC, and despite many advances in neonatal care the mortality and morbidity associated with NEC remains significant. In this article we review Near Infrared Spectroscopy (NIRS) as a method of measuring regional gut tissue oxygenation. We discuss its current and potential future appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…To date, no study has identified and validated the level of deoxygenation in the mesenteric tissue before the onset of NEC [35]. We could not assess the clinical value of the alteration in the mesenteric tissue oxygenation recorded during and after feeding because none of the enrolled infants developed NEC.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no study has identified and validated the level of deoxygenation in the mesenteric tissue before the onset of NEC [35]. We could not assess the clinical value of the alteration in the mesenteric tissue oxygenation recorded during and after feeding because none of the enrolled infants developed NEC.…”
Section: Discussionmentioning
confidence: 99%
“…The rSO 2 value is believed to reflect the perfusion and metabolism of the tissue being assessed, assessing the balance of local tissue oxygen supply and demand. Tissue microcirculation includes arteries, veins and capillaries, which means that rSO 2 represents a "weighted average" of these structures, with approximately 75-85% of the signal coming from the venous vessels [13][14][15]. The first conducted research allowed for the determination of penetration depth at approximately 1/3 of the emitter-detector distance [16].…”
Section: Introductionmentioning
confidence: 99%